2017
DOI: 10.1007/s00259-017-3849-3
|View full text |Cite
|
Sign up to set email alerts
|

Integrated 18F-FDG PET/MRI in breast cancer: early prediction of response to neoadjuvant chemotherapy

Abstract: F-FDG PET/MRI can be used to predict non-pCR after the first cycle of NAC in patients with breast cancer and has the potential to improve sensitivity by the addition of MRI parameters to the PET parameters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
34
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 34 publications
1
34
0
Order By: Relevance
“…Cho et al performed 18 F‐FDG PET/MRI in 26 breast cancer patients before and after the first round of chemotherapy and evaluated qualitative MRI parameters as well as quantitative PET and MRI parameters . While the qualitative MRI parameters were not found to be different between pathologic complete responders and pathologic noncomplete responders, reductions in total lesion glycolysis (TLG) and signal enhancement ratio (SER) were different between the two groups.…”
Section: Neoadjuvant Therapymentioning
confidence: 99%
“…Cho et al performed 18 F‐FDG PET/MRI in 26 breast cancer patients before and after the first round of chemotherapy and evaluated qualitative MRI parameters as well as quantitative PET and MRI parameters . While the qualitative MRI parameters were not found to be different between pathologic complete responders and pathologic noncomplete responders, reductions in total lesion glycolysis (TLG) and signal enhancement ratio (SER) were different between the two groups.…”
Section: Neoadjuvant Therapymentioning
confidence: 99%
“…Recently, a review focused on the value of FDG PET/CT as a response prediction tool in breast cancer [31]. Although the current study does not present a head-tohead comparison to a pure PET/CT approach, the data suggest that PET/MRI will most likely be superior since the MRI increased significantly the sensitivity as well as the specificity of PET [29].…”
mentioning
confidence: 80%
“…In this issue, a paper by Cho and coworkers reporting a prospective FDG PET/MRI study in breast cancer patients scheduled to receive neo-adjuvant chemotherapy is published [29]. In an earlier study, it was shown that simultaneous PET/ MRI can enable illustration of close interactions between glucose metabolism and pharmacokinetic parameters in breast This Editorial Commentary refers to the article https://doi.org/10.1007/ s00259-017-3849-3 cancer patients and the potential of this for response assessment was discussed [30].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Positron emission tomography/magnetic resonance imaging (PET/MRI) is a two-in-one hybrid imaging technology that could provide competitive advantages over PET/X-ray computed tomography (PET/CT), including superior soft tissue contrast, advanced options for multiparametric MRI and MR spectroscopy, superior motion-tracking capabilities, and reduced radiation exposure [1]. A number of studies reported that 2-deoxy-2-[ 18 F]fluoro-D-glucose ([ 18 F]FDG) PET/MRI has the potential to qualitatively and quantitatively improve tumor characterization in breast cancer [2,3]. Xin et al [4] also reported that PET/MRI could provide good image quality suitable for the detection of abdominal and pelvic tumors.…”
Section: Introductionmentioning
confidence: 99%